Gambaran Kepatuhan Diet dan Kepatuhan Pembatasan Cairan pada Pasien Hemodialisa di RSI Sultan Agung Semarang - Dewi Safitri; Mohammad Arifin Noor; Dwi Retno Sulistyaningsih (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Hemodialysis is a therapeutic method used to remove fluids and waste products from the body. This study aims to determine the description of diet compliance and compliance with fluid restrictions in hemodialysis patients. Method : This research is descriptive research, with a cross sectional approach. The patient sample size was 98 respondents with a sampling technique using total sampling. Measuring diet compliance using a questionnaire and measuring fluid compliance using measuring instruments (IDWG). Result : The results of this study show that the majority of respondents showed dietary compliance as much as 85.7%. This shows that the majority of respondents have good awareness in implementing dietary compliance. Respondents with light fluid compliance were 72.4%, moderate 25.5%, severe 2.0%. Conclusion : Dietary compliance and fluid compliance in hemodialysis patients shows that the majority of respondents have good awareness in implementing dietary compliance and fluid compliance.